2020
DOI: 10.1055/s-0040-1714095
|View full text |Cite
|
Sign up to set email alerts
|

Straws Don't Suck: Are Straws Dangerous after Endoscopic Skull Base Surgery?

Abstract: Objective Patients undergoing endoscopic endonasal surgery have historically been restricted from using straws postoperatively, due to the concern that this activity generates negative pressure. The objective of this study is to evaluate the pressure dynamics in the sinonasal cavity associated with the use of a straw. Methods Intracranial pressure catheters were placed in the nasal cavity of 20 healthy individuals. Pressure measurements were then recorded while participants drank liquids of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In a series of 20 healthy subjects, Reilly et al. found that drinking from a straw did not generate a significantly greater amount of negative intranasal pressure than did drinking from a cup, regardless of fluid viscosity (e.g., water, milkshake) 102 . Similar findings were also observed in the context of nasal occlusion.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…In a series of 20 healthy subjects, Reilly et al. found that drinking from a straw did not generate a significantly greater amount of negative intranasal pressure than did drinking from a cup, regardless of fluid viscosity (e.g., water, milkshake) 102 . Similar findings were also observed in the context of nasal occlusion.…”
Section: Resultsmentioning
confidence: 80%
“…Similarly, the evidence on straw use in patients after ESBS is limited. 6,102 Straw use has a theoretical risk of increasing sinonasal negative pressure and increasing CSF leak risk, which must be considered when counseling patients postoperatively. Although a prospective series by Reilly et al recently demonstrated straw use to not be associated with significant negative pressure in the nasal cavity (i.e., no significant difference compared to drinking from a cup), 102 straw use in ESBS has not been thoroughly investigated in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations